Odpowiedzi

2009-12-03T19:52:36+01:00
A) 2x²+20x+25=0

b) 6-2√3+2√3-2=0
po skróceniu wynosi 4

c) x²√2-4x-x-2√2=0
x²√2-5x-2√2=0

d) 2x√2+x²+4+x√2
1 2 1
2009-12-03T20:02:56+01:00
(2x+5)²=4x²+20x+25

(√3+1)(2√3-2)=6-2=4

(x√2+1)(x-2√2)=x²√2-4x+x-2√2=x²√2-3x-2√2

(x+√2)(2√2+x)=2x√2+x²+4+x√2=x²+3x√2+4
Najlepsza Odpowiedź!
2009-12-03T20:08:54+01:00
Zapisz w postaci sumy algebraicznej

(2x+5)² = 4x² + 20x + 25

Przekształć iloczyny na sumy

(∫3+1)(2∫3-2) = 6 - 2∫3 + 2∫3- 2)

(x∫2+1)(x-2∫2) = x²∫2 - 4x + x - 2∫2

(x+∫2)(2∫2+x) = 2∫2x + x² + 4 + x ∫2